UTILISATION OF ENSILED MAIZE STOVER AND CONCENTRATE SUPPLEMENTS BY WEST AFRICAN DWARF SHEEP (2013)
Maize Stover (MS), an abundant crop residue isa potential feed for ruminants. The nutritive value is reduced when left on the field without processing and preservation due to further lignification. The ensiling of MS with additives for preservation and use as feed for ruminant have not been adequately documented. Therefore, utilisation of ensiled MS and concentrate supplements byWest African Dwarf Sheep (WADS)was investigated. Two tonnes of MS were ensiled for 30 days using different additives (molasses, honey and sugar) at the rate of 50g kg-1 to obtain the following silages: MS and Molasses (MSM), MS and Honey (MSH), MS and Sugar (MSS) and MS only (control) which served as treatments. The pH, colour, odour and texturesilage characteristics were determined using standard procedures. Dry Matter (DM), Crude Protein (CP), ash, Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF) and Acid Detergent Lignin (ADL) of the ensiled MS were determined using standard techniques. Eight WADS were used to assess the silage acceptability using Coefficient of Preference (CoP) procedure. Nutritive value of the silages was determined using in vitro fermentation techniqueto obtain Total Gas Volume (TGV), methane and Dry Matter Degradability (DMD). Further, a mixture of the control (C)with Concentrate Supplements (CS) was fed to 20 WADS for 105 days in a completely randomised design as diets: A (75% C+ 25% CS), B (50% C + 50% CS), C (25% C + 75% CS), D (100% C) and E (100% CS) to assess Dry Matter Intake (DMI) and Daily Weight Gain (DWG). Blood was collected to determine Packed Cell Volume (PCV), Red Blood Cell (RBC), White Blood Cell (WBC), Total Blood Protein (TBP) and Blood Urea (BU). Data were analysed using descriptive statistics, correlation and ANOVA at P=0.05.The greengage colour, pleasant and fruity odour, firm texture and pH (3.5-3.7) were similar among the silages. The DM (31.6-35.3%), CP (7.9-8.9 %), NDF (68.6-69.9%), ADF (56.1-63.2%) and ADL (14.0-16.8%) were not significantly affected by the additives. Ash composition was significantly different such that it was lowest in MSH (6.3%). The silages were equally accepted by WADS with feed intake ranging from 517.1 to 558.2gDM/day and CoP between 0.95 and 1.03. The TGV: 31.7ml and41.0ml; methane: 16.09 % and 25.20 % respectively for MS (control) and MSS silages varied significantly.The DMI of control (242.26 g/day) without supplement was significantly lower than that of control with supplements while DWG (-19.1-81.9g/day) varied significantly among the treatments. An inverse relationship was observed between the inclusion level of control and DMI (r = -0.85). However, direct relationship was noticed between DMI and DWG (r = 0.95). The RBC (2.39-3.51x106μl), WBC (8.58-43.01x103 μl), BU (23.63-47.27mg/dl) and TBP (9.40-14.26g/dl) decreased significantly with increased inclusion ofcontrol but PCV (22.50-30.33%) was not significantly affected. Ensiled maize stover with concentrate supplements in a ratio of 3:1 respectively enhanced sheep performance and is therefore recommended for West African Dwarf sheep